2018
DOI: 10.1177/1046496418802362
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Social Simulation: Studying Group Dynamics on a Massive Scale

Abstract: Recent advances in artificial intelligence and computer science can be used by social scientists in their study of groups and teams. Here, we explain how developments in machine learning and simulations with artificially intelligent agents can help group and team scholars to overcome two major problems they face when studying group dynamics. First, because empirical research on groups relies on manual coding, it is hard to study groups in large numbers (the scaling problem). Second, conventional statistical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Collins has discussed the nature of prediction in his model and assessed various alternative predictions and explanations, but he argues that his 'model' fares better. Instead of going into whether Collins outpredicts these rival explanations, our main point here is that Collins' model has been tested by others using computational methods, including sometime collaborators (Hanemann 1987) but also others who build on and extend or improve upon his work (see e.g., Turchin 2019: 16-28) and use his ideas as part of more comprehensive-not just state-breakdown related-testing of theories using computational models. Collins' state breakdown model, as outlined in Fig.…”
Section: The Example Of Randall Collins and His State Breakdown Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Collins has discussed the nature of prediction in his model and assessed various alternative predictions and explanations, but he argues that his 'model' fares better. Instead of going into whether Collins outpredicts these rival explanations, our main point here is that Collins' model has been tested by others using computational methods, including sometime collaborators (Hanemann 1987) but also others who build on and extend or improve upon his work (see e.g., Turchin 2019: 16-28) and use his ideas as part of more comprehensive-not just state-breakdown related-testing of theories using computational models. Collins' state breakdown model, as outlined in Fig.…”
Section: The Example Of Randall Collins and His State Breakdown Theorymentioning
confidence: 99%
“…Still, and this returns us to current limits, a major shortcoming of current AI-based models is that there is inadequate semanticisation. Both natural human language and formal mathematical language are used by social scientists to theorise, and both come with their own sets of strengths and weaknesses (Hanemann 1987). Formal language is more precise and facilitates automated symbol manipulation.…”
Section: The Systems We Need: Strengths and Gaps In Current Ai-systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial investigations centered around attempts to characterize discussions on GitHub in terms of their social purposes (the description in this section is based on Hoey et al, 2018 and, where more details on methods and results can be found). We used the Interaction Process Analysis (IPA) categories of Bales (1950) as a standard classification scheme for human actions in a group.…”
Section: Identifying Sentiments and Group Behaviours On Githubmentioning
confidence: 99%
“…Group dynamics is a study that describes the various forces that determine the behaviour of members and group behaviour that cause changes in the group to achieve common goals that have been set. Group dynamics are psychological relationships that take place together from group members, paying attention to human behaviour in small groups and the forces that exist in the group, the causes for the growth of these powers and their influence on individuals, groups and their environment (Hoey et al, 2018).…”
Section: Introductionmentioning
confidence: 99%